Isothermal crystallization kinetics of an industrial-grade Zr-based bulk metallic glass - Yang, Zerong; Al-Mukadam, Raschid; Stolpe, Moritz; Markl, Matthias; Deubener, Joachim; Körner, Carolin (Journal of Non-Crystalline Solids, 2021)
Bulk metallic glasses (BMGs), due to their amorphous structure, exhibit remarkable mechanical properties, and there is an increasing interest in their commercialization. For the industrial fabrication of BMG, knowledge about the isothermal crystallization kinetics of industrial-grade BMG is required. Previous investigations on isothermal crystallization kinetics are mainly based on high-purity samples with very good glass forming ability and/or mainly limited to the low temperature regime. In the present study, a systematic investigation on the isothermal crystallization kinetics of an industrial-grade Zr-based BMG (Zr59.3Cu28.8Al10.4Nb1.5 at.%, trade name: AMZ4) has been performed using conventional and flash differential scanning calorimetry. We report the time-temperature-transformation (TTT) diagrams of the AMZ4 with two different oxygen levels. The diagrams cover the temperature range from glass transition temperature up to liquidus temperature, that have the typical “C-shaped” noses. Faster crystallization of the higher oxygen level AMZ4 was observed, and the underlying mechanisms were investigated. The universal isothermal Johnson-Mehl-Avrami-Kolmogorov (JMAK) model was employed to model the isothermal crystallization kinetics. Satisfactory match was achieved between the experimental facts and the JMAK model, and the interfacial energies between the crystalline phase and liquid were determined as 0.04 J/m2 for the industrial-grade AMZ4. The crystallization fraction dependence of Avrami index and activation energy is studied and found to be neglectable in the JMAK modeling. The critical casting thicknesses were estimated based on the TTT diagrams.
Keywords: Crystallization kinetics; Bulk metallic glass; JMAK Model; Classical nucleation theory; Time-temperature-transformation diagram; Fast scanning calorimetry; Selective laser melting